(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
This research studies the growth rate of the cracks and accumulation damage of the fatigue for low carbon steel alloy with fixed and variable stresses amplitude. All tests were carried out under a stress ratio of (R=0.1) and at room temperature condition. Two test groups consisting of 12 flat samples were designed. The first group was tested under constant amplitude loads which aimed to study the rate of growth and the increasing of fatigue cracks by increasing the stresses exerted. The second group was tested under variable amplitude loads in the form of (decreasing) and (increasing- decreasing) loads. The aim was to study the effect of periodic strain ranges on the growth rate of cracks and fatigue life. The results of the constant amplitude loads proved that the increasing of the applied stress about 26% leads to reducing the fatigue strength and thus decreasing the fatigue life about 93%. In the case of the second group, which was carried under variable amplitude loads, the results were as follows: In case of variable amplitude loads in the form of (decreasing), Nf is up to 186000 cycles while in case (increasing- decreasing) loads, the number of courses required for the failure was Nf 151000 cycles.